Nilai-Nilai Pendidikan Islam dalam Buku “Orang Maiyah” Karya Emha Ainun Nadjib - Wardatul Ummah (Tarbawi: Journal of Islamic Education, 2020)
Today's education can be said to be alarming, as a person who is concerned in education we must not be trapped in material things, for example we judge the level of education of a person from the degree he has, how many degrees he has and where he got it, but today we do not see a more substantial state of "They". Let's look at school children at this time have reduced respect for older people and think more biased and smarter than others. In the context of learning, doctrination still occurs in each subject matter. Learning activities are more focused on the minimum level of thinking (low order thinking), the teacher's job is simply to at the same time prohibit students - without providing opportunities for independent learning. This kind of educational practice by Emha Ainun Nadjib is often criticized that schools are like factories that require product standardization.